From Antarctica to the subtropics: Contrasted geographical concentrations of selenium, mercury, and persistent organic pollutants in skua chicks (Catharacta spp.). (September 2017) - Carravieri, Alice; Cherel, Yves; Brault-Favrou, Maud; Churlaud, Carine; Peluhet, Laurent; Labadie, Pierre; Budzinski, Hélène; Chastel, Olivier; Bustamante, Paco
Abstract: Seabirds integrate bioaccumulative contaminants via food intake and have revealed geographical trends of contamination in a variety of ecosystems. Pre-fledging seabird chicks are particularly interesting as bioindicators of chemical contamination, because concentrations in their tissues reflect primarily dietary sources from the local environment. Here we measured 14 trace elements and 18 persistent organic pollutants (POPs) in blood of chicks of skuas that breed in four sites encompassing a large latitudinal range within the southern Indian Ocean, from Antarctica (Adélie Land, south polar skua Catharacta maccormicki ), through subantarctic areas (Crozet and Kerguelen Islands, brown skua C. lonnbergi ), to the subtropics (Amsterdam Island, C. lonnbergi ). Stables isotopes of carbon (δ 13 C, feeding habitat) and nitrogen (δ 15 N, trophic position) were also measured to control for the influence of feeding habits on contaminant burdens. Concentrations of mercury (Hg) and selenium (Se) were very high at all the four sites, with Amsterdam birds having the highest concentrations ever reported in chicks worldwide (4.0 ± 0.8 and 646 ± 123 μg g −1 dry weight, respectively). Blood Hg concentrations showed a clear latitudinal pattern, increasing from chicks in Antarctica to chicks in the subantarctic and subtropical islands. Interestingly, blood Se concentrations showed similar between-population differences to Hg, suggesting its involvement in protective mechanisms against Hg toxicity. Chicks' POPs pattern was largely dominated by organochlorine pesticides, in particular DDT metabolites and hexachlorobenzene (HCB). Skua chicks from subantarctic islands presented high concentrations and diversity of POPs. By contrast, chicks from the Antarctic site overall had the lowest concentrations and diversity of both metallic and organic contaminants, with the exception of HCB and arsenic. Skua populations from these sites, being naturally exposed to different quantities of contaminants, are potentially good models for testing toxic effects in developing chicks in the wild. Graphical abstract: Highlights: Blood trace elements and POPs were measured in southern Indian Ocean skua chicks. Latitudinal trends in skua chicks' blood burdens were evident for Hg, Se and HCB. Subtropical chicks had the highest Hg and Se burdens among birds from remote sites. Plasma HCB burdens were relatively high, while several other POPs had low occurrence. Toxicological studies are needed for As, Hg, Se and HCB in these skua populations. Abstract : Skua chicks from four widely separated sites within the southern Indian Ocean had contrasted blood metallic and organic contaminant patterns, and very high Hg and Se burdens.